Photoresponsive peptide delivery systems and methods of use thereof - WANG WEIPING; LIANG XIAOLING; LI JIA; ZHOU YANG (2025)
Provided herein are photoresponsive prodrugs comprising an active agent conjugated to a photoresponsive group, and nanoparticles formed in which a photoresponsive prodrug is co-assembled with a polymer. Also provided are methods of treating a subject comprising administering a photoresponsive prodrug or nanoparticle to the subject and irradiating a target site with a light source. 本文提供了包含缀合至光响应基团的活性剂的光响应性前药，以及其中光响应性前药与聚合物共组装而形成的纳米颗粒。还提供了治疗受试者的方法，包括向受试者施用光响应性前药或纳米颗粒，并用光源照射目标部位。